2022
DOI: 10.1002/suco.202100584
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of a compressive strength model for FRP‐confined damaged concrete columns based on the Drucker–Prager yield criterion

Abstract: Fiber reinforced polymer (FRP) has been widely used in repairing and strengthening of damaged concrete columns due to its excellent material properties. Most of the existing compressive strength models for FRP-confined concrete columns have been established through regression analyses of experimental data, and only a few models were established based on theoretical derivation. Therefore, to extend these compressive strength models based on theoretical derivation, a new strength model based on the Drucker-Prage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…The concrete-damaged plasticity model was used to predict the nonlinear behavior of a PCB bridge. [24][25][26][27] This model assumes a non-associated plastic flow potential using the Drucker-Prager hyperbolic function for the flow potential. The damage factors of the tensile and compressive parameter values were determined based on previous studies, as shown in Figure 7.…”
Section: Concretementioning
confidence: 99%
“…The concrete-damaged plasticity model was used to predict the nonlinear behavior of a PCB bridge. [24][25][26][27] This model assumes a non-associated plastic flow potential using the Drucker-Prager hyperbolic function for the flow potential. The damage factors of the tensile and compressive parameter values were determined based on previous studies, as shown in Figure 7.…”
Section: Concretementioning
confidence: 99%
“…In order to identify the unknown constants of A and B, the Drucker-Prager yield criterion can be expressed in terms of principal stresses, as follows 69,70 ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi…”
Section: Numerical Modelling Of Three-point Bending Testsunclassified
“…In order to identify the unknown constants of A and B, the Drucker-Prager yield criterion can be expressed in terms of principal stresses, as follows 69,70 …”
Section: Numerical Modelling Of Three-point Bending Testsmentioning
confidence: 99%
“…Specially, the compressive strength has been gained a significant research interest, for example see. [4][5][6] Providing a statistical evaluation, a database of publications on compressive behavior of FRP-confined concrete columns is collected. The database includes more than 50 publications from 1997 to 2021.…”
Section: Introductionmentioning
confidence: 99%